Identidade e redesignação de gênero: aspectos da personalidade, da família e da responsabilidade civil - Cunha, Leandro Reinaldo da (2014)
This thesis pursuit a wide appreciation about gender figure in brazilian civil law, based in comparative law, searching a review of current social parameters and the attention that legal system gives to the theme, with the ultimate objective to configure gender identity like a right of personality relegated by State, as like the consequences of this attitude. At first it s necessary to show some points about sexuality and gender identity, setting understanding criteria about theme to avoid misunderstandings of treating different things like equal, as well as equate absolutely distinct situations, passing, further, to constitutional principles's comprehension that support the proposition. A more accurate analysis shows that gender identity is a widely overlooked issue by the atual legal system, however it had scarce regulations with low amplitude and lots of law projects that recognize gender identity like right of personality stationary in national Congress, revealing a manifested delay of our country, because the theme is already written in the foreign legislation since the mid-twentieth century. The treatment given in national legal system to gender identity confers to transgender and to intersexual a huge marginalization condition, hindering that this social group can live fully its citizenship, in an evident attack to commandment inherent of the Democratic Law State, hitting frontally human dignity principle, as so rights personality s elements. Garantee to everyone all conditions to a dignity life in society, with no bias and discrimination, respecting fundamental rights stated in Federal Constitution, as well the criteria regulamented in international agreements and declarations of human righs is a obligation of all State that have the human dignity as one of your basis. State s delay to garantee respect to human being with all of your characteristics and idiosyncrasies are a serius omission that cannot perpetuate itself